2018
DOI: 10.1038/s41467-018-03925-2
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidins prime platelets to mediate arterial thrombosis and tissue inflammation

Abstract: Leukocyte-released antimicrobial peptides contribute to pathogen elimination and activation of the immune system. Their role in thrombosis is incompletely understood. Here we show that the cathelicidin LL-37 is abundant in thrombi from patients with acute myocardial infarction. Its mouse homologue, CRAMP, is present in mouse arterial thrombi following vascular injury, and derives mainly from circulating neutrophils. Absence of hematopoietic CRAMP in bone marrow chimeric mice reduces platelet recruitment and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 68 publications
5
106
0
Order By: Relevance
“…LL37 directly induced platelet aggregation in a concentrationdependent manner, notably, 20 mM LL37 induced 100% aggregation ( Figure 1F). In line with a recent study, 21 in our experiments, LL37 failed to induce aggregation in human PRP (supplemental Figure 1). Similarly, to determine whether LL37 influences inside-out signaling to integrin aIIbb3 and a-granule secretion, the level of fibrinogen binding and P-selectin exposure was measured respectively using human isolated platelets and PRP by flow cytometry.…”
Section: Ll37 Induces Platelet Activationsupporting
confidence: 93%
See 2 more Smart Citations
“…LL37 directly induced platelet aggregation in a concentrationdependent manner, notably, 20 mM LL37 induced 100% aggregation ( Figure 1F). In line with a recent study, 21 in our experiments, LL37 failed to induce aggregation in human PRP (supplemental Figure 1). Similarly, to determine whether LL37 influences inside-out signaling to integrin aIIbb3 and a-granule secretion, the level of fibrinogen binding and P-selectin exposure was measured respectively using human isolated platelets and PRP by flow cytometry.…”
Section: Ll37 Induces Platelet Activationsupporting
confidence: 93%
“…Immediately prior to the submission of this manuscript, a recent study demonstrated the functional impact of LL37 in priming platelets and inducing thromboinflammatory conditions, although the molecular mechanisms that regulate such effects were not fully established. 21 However, in this study, we have investigated the impact of LL37 in the modulation of platelet reactivity, thrombosis, and hemostasis under physiological conditions and uncovered the functional dependence of LL37 on FPR2/ALX in platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil extracellular traps, containing decondensed chromatin and antimicrobial proteins, stimulate the intrinsic pathway of coagulation, increase platelet-dependent thrombin generation, activate platelets and increase thrombi size. 11,19,31,32 Thus, activated neutrophils play a procoagulant role in arterial thrombosis. Activated platelets excite neutrophils, which, in return, reinforces platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thrombosis in vivo was analyzed following a FeCl3‐induced vessel injury in the mouse common carotid artery as described before . Briefly, mice were anesthetized using 2% isoflurane and intraperitoneal injection of fentanyl (0.05 mg/kg), midazolam (5 mg/kg), and medetomidine (0.5 mg/kg).…”
Section: Methodsmentioning
confidence: 99%